Implementation of the Decree of the Head of BPJPH No. 20 of 2023 Concerning Amendments to the Decree of the Head of BPJPH No. 57 of 2021 and LPPOM MUI Number SK 46/DIR/LPPOM MUI/XII/14 Regarding the Practice of Buying and Selling Food with Inappropriate Names (Case Study of Food Venues in Binjai City) - Deva Anggraini; Muhammad Nur Iqbal (SEAN Institute, 2026)
This study aims to analyze the implementation of the Decree of the Head of BPJPH Number 20 of 2023 and LPPOM MUI SK Number 46/DIR/LPPOM MUI/XII/14 regarding the practice of naming inappropriate food products in culinary Micro, Small, and Medium Enterprises (MSMEs) in Binjai City. The phenomenon of using controversial or inappropriate product names, such as “Nasi Goreng Satan,” reflects a growing trend in marketing strategies that prioritizes uniqueness and consumer attraction, yet raises concerns in terms of compliance with the halalan thayyiban principle. In particular, such naming practices pose administrative and ethical challenges in fulfilling halal certification requirements, especially in relation to decency, Islamic values, and public perception. This research employs a qualitative method with a socio-legal approach, aiming to examine not only the regulatory framework but also its implementation in real social contexts. Data were collected through in-depth interviews with business actors and Halal Product Process Assistants (PPPH), field observations of culinary MSMEs, and analysis of relevant regulatory documents. The data analysis technique utilizes SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to identify key issues and formulate appropriate mitigation strategies for business actors. The results indicate that there is a significant gap between existing halal product naming regulations and actual branding practices in the field. This gap is primarily caused by the low level of literacy and understanding among MSME actors regarding halal regulations, as well as concerns about losing brand identity and commercial attractiveness when changing product names. Furthermore, weak socialization and limited assistance contribute to the persistence of such practices. To address these challenges, this study proposes several mitigation strategies, including strengthening halal literacy through digital platforms and social media, enhancing persuasive and continuous assistance by PPPH, and reconstructing brand identity that aligns with ethical and decency values ​​while maintaining market competitiveness. These strategies are expected to support MSMEs in achieving halal compliance without compromising their business sustainability and branding effectiveness